2014
DOI: 10.3325/cmj.2014.55.452
|View full text |Cite
|
Sign up to set email alerts
|

Emigration-related attitudes of the final year medical students in Croatia: a cross-sectional study at the dawn of the EU accession

Abstract: AimTo investigate the emigration-related attitudes of final year medical students in Croatia at the dawn of the EU accession in 2013.MethodsAll final-year medical students at four Croatian medical schools (Zagreb, Rijeka, Split, and Osijek) were invited to participate in a cross-sectional survey on emigration attitudes.ResultsAmong 260 respondents (response rate 61%), 90 students (35%) reported readiness for permanent emigration, expecting better quality of life (N = 22, 31%), better health care organization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(17 reference statements)
0
12
0
2
Order By: Relevance
“…60% of medical residents from Lithuania stated that they intended to emigrate, 15% of them permanently [27], and only 45% of the Czech physicians are contemplating emigration [28]. One third of the final year medical students from Croatia reported their willingness to permanently leave the country in search of employment elsewhere [10]. In 2004, surveys conducted in Central and Eastern Europe found that 10.4% of Polish, 15.6% of Czech, and as many as 24.7% of Hungarian physicians contemplated migration [12].…”
Section: Discussionmentioning
confidence: 99%
“…60% of medical residents from Lithuania stated that they intended to emigrate, 15% of them permanently [27], and only 45% of the Czech physicians are contemplating emigration [28]. One third of the final year medical students from Croatia reported their willingness to permanently leave the country in search of employment elsewhere [10]. In 2004, surveys conducted in Central and Eastern Europe found that 10.4% of Polish, 15.6% of Czech, and as many as 24.7% of Hungarian physicians contemplated migration [12].…”
Section: Discussionmentioning
confidence: 99%
“…Structural factors included problems caused by misdirected policies and regulations of the Ministry of Health, lack of optimal utilization of graduates, problems with the education system and problems in some areas of research. Kolčić et al, introduced the structure of Croatia’s healthcare organization as a main reason for inclination of medical students to migrate ( 27 ). A study conducted in Pakistan also showed that working in a better healthcare organization provided motivation for migration ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 Pozitivan učinak priljeva vrhunskih stručnjaka u odnosu na zemlje odredišta očigledan je, s obzirom na to da oni svojim znanjem i radom pridonose povećanju stupnja razvoja zemlje, njene proizvodnje, te standarda stanovništva. 32 Imajući na umu prethodno navedene posljedice iseljavanja u odnosu na matičnu zemlju, evidentno je kako je odljev mozgova pojava koja ima dva posve suprotna učinka: ona istovremeno uzrokuje usporavanje ili čak nazadovanje gospodarstva matične zemlje i napredak gospodarstva zemlje odredišta. 33 Aktualan rastući trend odlaska visokoobrazovanih iz Srednje i Istočne Europe u Zapadnu Europu najbolje prikazuje ambivalentnost učinka pojave odljeva mozgova.…”
Section: Odljev Mozgova -Faktori Privlačenja (Pull Factors) I Učinci unclassified
“…29, str..73-85. 32 Kostanjevečki Tatjana, Psihološki aspekti nezaposlenosti: Odljev mozgova, Zbornik radova XII. ljetne psihologijske škole, Silba, 2002.…”
Section: Iseljavanje Iz Hrvatske Nakon Pristupanja Europskoj Unijiunclassified